MENINGKATKAN PEMBELAJARAN ROLL DEPAN DENGAN ALAT BANTU BOLA LONCENG PADA SISWA KELAS V SD MUHAMMADIYAH 2 KOTA TEGAL (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the effort to improve the learning aids roll the ball forward withbells on fifth grade students of SD Muhammadiyah 2 Tegal in 2013. The research method used is a classaction research (action research)The results obtained in class V SD Muhammadiyah 2 Tegal, amounting to 28 students are, (1) In the pre-cycleof learning activities of students during the learning process gymnastics floor front was roll students completedas many as 16 percent of students with 57.14%, and students have not completed as much as 12 percent ofstudents with 42.86%. (2) In the study by using a ball tool bells in the first cycle to be completed by 25 studentswith a percentage of 89.29%, students who have not completed as much as 3 percentage with 10.71%. (3) Theresults of research on students completed 2 cycles to 28 with a percentage of 100%.From the available data it can be concluded that the use of a bell ball aids in learning gymnastics floor front rollcan significantly improve learning outcomes for students of classes V SD Muhammadiyah 2 Tegal, studentslooked interested, active, enthusiastic, pay attention and be able to follow the learning process roll